Using particle tracking and genetic approaches to infer population connectivity in the deep-sea scleractinian coral Deltocyathus magnificus in the South China sea. (July 2020) - Liu, Shang-Yin Vanson; Hsin, Yi-Chia; Cheng, Yu-Rong
Abstract: Deep-sea scleractinian corals are distributed from 50 m to 6000 m depths. Under global environmental changes ( e.g ., ocean acidification) and anthropogenic effects ( e.g ., bottom trawling), deep-sea scleractinian coral assemblages are considered to be at great risk of losing fitness by allocating increased energy toward calcification. For marine organisms, population persistence and species resilience depend largely on connectivity with neighbors. Therefore, as anthropogenically induced declines in deep sea populations grow, there is an urgent need to study their dispersal patterns through an integrated approach that can indirectly infer connectivity among populations. In the present study, we incorporated passive particle tracking and genetic structure analyses to reveal the connectivity of the deep-sea coral Deltocyathus magnificus among six sites in the South China Sea. Our results indicate a genetic/connectivity break between western Dongsha (~200 m depth) and Macclesfield Bank populations (~400 m depth) and suggest that the hydrodynamic regime may play a more important role than isolation by depth. The results of this study provide not only insights into deep-sea coral dispersal patterns but also valuable information for future deep-sea coral conservation and management. Highlights: Our results indicate a genetic/connectivity break between western Dongsha (~200 m depth) and Macclesfield Bank populations (~400 m depth) by using integrated approaches. D. magnificus is a solitary coral with sexual recruits being the main source of local population replenishment. The eddy system and seasonal changes in current direction of the northeast South China Sea play important role on the connectivity of  D. magnificus .